2000
DOI: 10.1099/00221287-146-6-1256
|View full text |Cite
|
Sign up to set email alerts
|

PCR-based detection of mobile genetic elements in total community DNA

Abstract: USs of Haemophilus or Neisseria, then they would have been detected even if present with a moderate degree of degeneracy. If such a sequence were to be non-continuous then we would also have expected to detect the component parts as long as they were themselves sufficiently conserved. We were unaware of the papers on Acinetobacter. However, Acinetobacter is quite distinct from the other Gram-negative spp. with regard to DNA uptake and its very high transformability by plasmids, and therefore lies outside of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
52
0

Year Published

2001
2001
2013
2013

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 50 publications
(56 citation statements)
references
References 2 publications
4
52
0
Order By: Relevance
“…Traditionally, most attention has focused on plasmids and transposons. This is particularly true for environmental microbiology (24). However, since integrons have recently been demonstrated to occur in the chromosomes of diverse bacterial species (22) and integron integrases are recoverable from environmental samples (18), we reasoned that integrons are widespread in natural environments.…”
mentioning
confidence: 99%
“…Traditionally, most attention has focused on plasmids and transposons. This is particularly true for environmental microbiology (24). However, since integrons have recently been demonstrated to occur in the chromosomes of diverse bacterial species (22) and integron integrases are recoverable from environmental samples (18), we reasoned that integrons are widespread in natural environments.…”
mentioning
confidence: 99%
“…PCR amplification of DNA which was directly extracted from environmental samples with primers targeting replicon or resistance gene sequences, when combined with Southern blot hybridization, enables their rapid and specific detection. While PCR-based detection of MGE and resistance genes in community DNA is an ideal method to analyze many samples for the presence and abundance of the sequence targeted (23), no information is obtained on its genomic context. For this, the isolation of the respective MGE is essential.…”
mentioning
confidence: 99%
“…In contrast, several studies have previously indicated widespread dissemination of the clinical IncP plasmid RK2 (Gotz et al, 1996 ;Smalla et al, 2000 ;Sobecky et al, 1997). Results from our comparative analysis of the putative Rep proteins in this study, together with those from previously characterized plasmid replicons, indicates that both RCR-and theta-replicating plasmids are to be found in marine isolates.…”
Section: Discussionmentioning
confidence: 94%